Mediation of Criminal Cases as an Effort to Settle Criminal Actions Based on Local Wisdom in Indonesia - Budisetyowati, Dwi Andayani; Joko Sriwidodo; Rr. Dijan Widijowati; Juanda (Dinasti Research, 2023)
Penal mediation is carried out to bring together criminal offenders and victims, so this penal mediation is often also known as